2022
DOI: 10.1177/0309524x221118684
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of wind energy resources from high rise building for micro wind turbine: A review

Abstract: Micro wind turbine is a technology that is used to generate electricity in urban areas. The purpose of this review paper is an analysis of micro wind turbines on high-rise buildings. High-rise buildings are used as towers for micro wind turbines. Here is an analysis of the wind map of India for installing wind turbines. With the help of wind maps, the behavior of wind at different heights has been studied. The result of this study is to analyze how much wind power is generated in different states of India. At … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…Installation of wind turbines in areas with wind speeds of less than 5 m s −1 is not economically viable. The power coefficient C P of the wind turbines was determined from equations (11) and (12).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Installation of wind turbines in areas with wind speeds of less than 5 m s −1 is not economically viable. The power coefficient C P of the wind turbines was determined from equations (11) and (12).…”
Section: Resultsmentioning
confidence: 99%
“…An in-depth review of the literature on the analysis of micro-turbine installations on high-rise buildings has revealed that these structures act as towers. The author mentioned that these micro wind turbines were installed in nine states of India for domestic use [11]. The review presented a comprehensive overview of small-scale wind turbines, noting that the installation of a large wind farm has a considerable impact on the climate, thus making micro-turbines more suitable for home use [6].…”
Section: Introductionmentioning
confidence: 99%
“…In the face of the evolving global energy structure and the escalating energy demand, wind power generation has attracted significant attention from countries worldwide, showcasing a sustained upward trajectory [1]. However, the inherent randomness and volatility of wind speed patterns pose substantial constraints on the large-scale integration of wind power generation in grid scheduling and stable operation due to natural environmental conditions [2].…”
Section: Introductionmentioning
confidence: 99%
“…A micro wind turbine (MWT) is a type of small-scale wind turbine used to generate electricity for residential or small commercial use (Wilberforce et al, 2023). MWTs have gained popularity in recent years as a way to reduce energy costs and increase energy independence (Kumar & Prakash, 2023). Advances in blade design, control systems, and materials technology have improved the energy conversion efficiency of MWTs and reduced their cost (Ayhan & Sağlam, 2012).…”
Section: Introductionmentioning
confidence: 99%